Stick slip characteristics analysis of drill string system with longitudinal and torsional coupling tool. (19th March 2022) - Tian, Jialin; Liu, Gang; Song, Haolin; Liu, Chenghang; Wen, Feng
Abstract: Due to the complexity and uncertainty of downhole conditions during drilling, the torsional vibration generated at the drill bit may cause the bottom hole assembly (BHA) to excite high frequency longitudinal vibration, which may lead to the longitudinal bounce of the drill string in severe cases. The excessive vibration will seriously affects the service life of the drill bit or other downhole tools. To avoid these problems and reduce the stick-slip phenomenon, this paper proposed an innovative longitudinal-torsional coupling tool, which can generate appropriate coupling vibration. With analysis of working mechanism, theoretical research includes establishment of dynamic model of BHA connected with the tool. The cases study is carried out based on Lagrangian theory. The results show the tool can effectively suppress stick-slip vibration. By adjusting the internal design parameter, the innovative design can achieve appropriate vibration, which can enable the drilling smoother, increase the mechanical efficiency, and reduce the wear of drill bit. The innovative design can provide reference for avoiding downhole accidents and improving of drilling safety. The theoretical research results can present new ideas for the development of drill string dynamics under new situations.